The assessment of land exploitation by enumerating microbial population: Case study in several locations at Dieng Plateau - Sumarsih, Sri; Virgawati, Sari (Journal of Tropical Life Science, 2013)
Agricultural intensification program in Indonesia which is carried out by using high yield variety, high chemicals use and soil disturbances tends to trigger land exploitation. Land exploitation, performed without considering the lands capability can generate degradations on the land itself. Various methods have been used to determine land exploitation level, including evaluation of soil microbe resources as on soil component. This research is aimed to assess land exploitation level, based on the amount of microbial population. The result of this research is expected to add the soil quality standard criteria. In the case study performed in Dieng plateau, representative soil sampling method was used. The amount of microbial population can be enumerated using plating and MPN method. Based on nutrient availability to indicate the soil biological characteristics, the soil under the trees, shrub, and Colocasia were classified as â€œbelow normalâ€, and the soil under the grass, tobacco, cabbage and potato were classified as normal. It shows that the land exploitation at the agricultural soils were still in the range of its land capability.